A Consideration of a Series of X-rays of Asian Pivoted Matchlock Mechanisms. (2013) - Bennett, Natasha
Abstract : A series of x-rays of pivoted matchlock mechanisms from across Asia, ranging from the 17th to the 19th centuries, is examined to assess whether studying the internal components of these lock mechanisms can help with the classification of weaponry and further our understanding of how firearms technology was disseminated within Asia. Some discernible pattern of regional variation indicates that many Asian pivoted matchlocks may have progressed beyond the Turkish lock popularised in the 16th and 17th centuries; such developments may offer at least a partial explanation for why matchlocks remained in use as viable weapons until the 19th century in areas such as Arabia and India. Possibilities for establishing a broad typological classification of matchlock mechanisms are explored.